2008
DOI: 10.12693/aphyspola.114.1139
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Resonant Polaron in a Self-Assembled Quantum Dot

Abstract: We calculate numerically the spectrum of a polaron in a quantum dot in the region of resonance with two-phonon states. We show that the experimental data can be reproduced by a model that does not depend on any adjustable parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Its description is nontrivial since there are no direct matrix elements coupling those states. In our recent works [4,5], we have shown that such a resonance can be accurately modeled using the Fröhlich coupling Hamiltonian with standard (bulk) values of material parameters, contrary to earlier suggestions [6].…”
Section: Introductioncontrasting
confidence: 66%
“…Its description is nontrivial since there are no direct matrix elements coupling those states. In our recent works [4,5], we have shown that such a resonance can be accurately modeled using the Fröhlich coupling Hamiltonian with standard (bulk) values of material parameters, contrary to earlier suggestions [6].…”
Section: Introductioncontrasting
confidence: 66%
“…On the other hand, not accounting for 3-phonon states moves the resonance to higher magnetic fields and produces nonexistent polaron branches in the resonance area (See Ref. 21 for more details). We have also checked to what extent the numerical results depend on our choice of the l z /l 0 ratio.…”
Section: Magnetopolaron Resonancesmentioning
confidence: 99%
“…On the other hand, not accounting for 3-phonon states moves the resonance to higher magnetic fields and produces nonexistent polaron branches in the resonance area (See Ref. 21 for more details).…”
Section: Magnetopolaron Resonancesmentioning
confidence: 99%